Criminal Liability of Perpetrators of Health Care Malpractice - Andi Mirza; Dahlan; Teuku Muttaqin Mansur (International Journal of Law and Society, 2025)
Health care is a fundamental right of every citizen guaranteed by the constitution and various laws and regulations. However, in practice there are still cases of health care malpractice that often occur, either due to negligence, carelessness, lack of competence, or violation of professional standards. Such actions not only have an impact on the physical and psychological harm of patients, but also raise questions regarding the legal responsibility of the perpetrators, especially in the criminal realm. The problems in this study are how health care malpractice in the perspective of criminal law and how criminal liability for health care malpractice. This research uses normative juridical research method with statute approach and conceptual approach. The results showed that health care malpractice must be viewed as a criminal offence that can be subject to criminal liability in accordance with the provisions in the Criminal Code, Law Number 17 of 2023 concerning Health, and other regulations.